Communication, construction and community - Price, A; Price, Alison (2000)
This study examines the teaching and early learning of addition in primary classrooms. The relationship between teaching and learning is examined at the level of classroom interaction, in the completion of mathematical tasks. The mathematics lessons of two classes in each of two schools were observed over a period of six months, involving four teachers and the 4, 5 and 6 year old children in their classes. The mathematical focus of the study was the learning of addition, one of the first formal mathematical concepts taught in school. This formed a basis for exploring the factors involved in the teaching of mathematics to young children, and their learning. The methodology is qualitative, with participant observation the main method of data collection. Detailed fieldnotes were taken of all mathematics lessons observed; short unstructured interviews with teachers were carried out before and after the lessons. The children's understanding of number concepts and addition was assessed at both the beginning and the end of the observation period. The data was analysed using a grounded theory approach, which produced patterns of recurring variables. Analysis of these variables, influenced by the theoretical perspectives of the researcher, provided analytical pictures of teaching and learning, from which the findings emerged. The study highlights the complexity of the classroom for teachers and young children, where curriculum considerations, understanding of the mathematics concepts, social interaction and integration into the community of the classroom, vie for attention. It indicates that children are more likely to make sense of mathematics when the number curriculum is taught with a view to its complexity, rather than broken down into simple steps; the problems young children have learning to use mathematical symbols; and that the use of story is important in helping especially the youngest children understand mathematics. This was a small scale study, but provides a 'thick description' of teaching and early learning of addition, which can form a basis for future studies. Key Words: addition, early mathematical development, primary school, constructivism, socio-cultural theory, situated cognition, symbols, real world scripts, narrative.